Elephant boy and robogirl - Government Information Office; Public Television Service ([Taiwan : Public Television Service, 2006)
The story abaout 2 children with disabilities. He is 8 years old and suffers from multiple handicaps. He must eat through his nose, and cannot speak. Though constantly in pain, he is happy and kind. He loves to imitate elephants and expresses himself joyfully. She is 8 years old and suffers from cerebral palsy. It takes her 90 seconds to take just 3 steps. Her body is stiff like a machine, and moving is excruciating
DVD Format
Subtitles in Tradisional Chinese, English, Francais and Espanol
Keywords: Children with disabilities -- Taiwan; Children with disabilities -- Care -- Taiwan